New histories of political violence and revolutionary terrorism in modern South Asia. Issue 3 (3rd July 2019) - Amstutz, Andrew; Elam, Daniel; Choudhury, Rishad; Banerjee, Mou; De, Rohit; Silvestri, Michael; Maclean, Kama; Ghosh, Durba
ABSTRACT: This book round table discusses two recent monographs on political violence and revolutionary terrorism in late colonial India, Kama Maclean's A Revolutionary History of Interwar India: Violence, Image, Voice and Text (2015) and Durba Ghosh's Gentlemanly Terrorists: Political Violence and the Colonial State in India, 1919–1947 (2017). Maclean's A Revolutionary History of Interwar India uncovers how revolutionaries in Punjab and northern India reshaped the goals and tactics of the Indian independence movement, especially the policy of nonviolence. Ghosh's Gentlemanly Terrorists explores the relationship of political violence in Bengal to the development of the modern nation-state in India. Both Ghosh and Maclean rethink the conventional narrative of the Indian freedom struggle and connect local developments in South Asia to global trends in anticolonial resistance and to larger conversations about the relationship between democracy and surveillance. In the five review essays, Daniel Elam, Rishad Choudhury, Mou Banerjee, Rohit De, and Michael Silvestri assess the impact of these two monographs on South Asian history, legal studies, histories of religion, studies of anticolonial movements, and British imperial historiography. In their responses, Maclean and Ghosh assess the challenges of writing histories of revolutionaries in the present in relation to the anticipated futures of the revolutionaries themselves.